Pride and panic : Russian imagination of the West in post-Soviet film - Hashamova, Yana (Intellect, 2007)
Through the looking-glass of Russian national cinema, Pride and Panic explores Russia's anxious adjustment towards the expansion of Western culture. Russian film is shown, in both its creation and perception, to expose the intriguing dynamics of societal psychological conditions.